Prototype Automatic Chicken Feeding Equipment at Putri Ungul Sentosa Farm - Kusban*, Muhammad; Kumala, Citra Nur (Universitas Syiah Kuala, 2023)
Indonesia has various economic sectors, including animal husbandry. One of the most numerous farms in Indonesia is chicken farming. One type of chicken farming is laying hens. The success of the breeding itself has various factors, including feeding. With the increasing need for quality feed and efficient feeding systems, there is a need for smarter and more automated chicken feeders. This farm has a problem with uneven feeding, therefore this research will develop automatic chicken feed so that the distribution of chicken feed can be made evenly using an IoT control system. This tool uses the main components in the form of stepper motors and stervo motors, where stepper motors are used as drivers of chicken feed containers while servo motors are used to open or close chicken feed doors. This tool will work with the time that has been set via a smartphone on the bylnk application in the morning and evening. The test results of this automatic feeder take approximately less than 2 minutes, and the weight is reduced between 1.2 - 1.6 kg.